PENGARUH MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, EXTENDING (CORE) TERHADAP PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI GELOMBANG BUNYI KELAS VIII DI SMPN 13 PEKANBARU - Nurfitasari, Cici; Irianti, Mitri; Sahal, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe and determine the effect of the CORE learning model on students conceptual understanding of class VIII sound wave material in SMPN 13 Pekanbaru. The kind of research use is quasi-experimental design is intact research group comparison. The subject of study is learners class VIII SMPN 13 Pekanbaru academic year 2018 /2019, consisting of class VIII.9 as a class the experiments were 35 students and class VIII.8 as a class control by 35 the number of students. Research instruments used is about a test understanding concept. Engineering data collection in this research by giving a test understanding the concept of after learning held on second class. The Data is analysed in descriptive to see the results of the percentage on understanding the concept and analysed in inferential using the T-test. The result showed that there are significant differences between understandings the concept of students on a CORE learning model applies with class conventional who apply the sound waves to the matter. Understanding the concept of class experiment score of average higher than class control. Based on the research so that it can be concluded that CORE learning model to understanding the concept of students to the matter the sound waves class VIII SMPN 13 Pekanbaru.Key Words: CORE Model, Understanding of Concepts, Sound Waves